1996
DOI: 10.1097/00005392-199612000-00044
|View full text |Cite
|
Sign up to set email alerts
|

Clean Intermittent Catheterization in Boys Using the Lofric Catheter

Abstract: In boys the LoFric catheter appears to cause less trauma. Although it is not reusable and is more expensive than the standard catheter, satisfaction is higher with the LoFric device and for select patients it has significant advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 12 publications
1
41
1
1
Order By: Relevance
“…It is worth highlighting that most of the children did not use any type of lubrication for the traditional catheter in their daily use, which was kept during the study in order to facilitate the evaluation without influencing its results. Differently from this study, in terms of statistical significance, but similarly to our findings, some studies observed higher levels of convenience and comfort attributed to the prelubricated catheter, exactly because this device does not require lubrication, which facilitated the procedure (15) .…”
Section: Rev Esc Enfermsupporting
confidence: 79%
See 3 more Smart Citations
“…It is worth highlighting that most of the children did not use any type of lubrication for the traditional catheter in their daily use, which was kept during the study in order to facilitate the evaluation without influencing its results. Differently from this study, in terms of statistical significance, but similarly to our findings, some studies observed higher levels of convenience and comfort attributed to the prelubricated catheter, exactly because this device does not require lubrication, which facilitated the procedure (15) .…”
Section: Rev Esc Enfermsupporting
confidence: 79%
“…In the literature review, only one study (15) evaluated the cost of the catheters and also observed a significant difference between the values -US$ 576.00 and US$ 30.60, respectively, for the pre-lubricated and traditional catheters, rather higher than those observed in our study (US$ 464.32 and US$ 2.46, respectively (c) ). Despite this fact, and since the pre-lubricated catheter is not distributed by the Unique Health System in the country, by evaluating the Brazilian reality, and especially the reality of the children assisted by the Hospital Darcy Vargas, it would not be possible for families in general to keep up the use of the pre-lubricated catheter at their own expense, as the monthly cost would correspond to 2.3 minimum salaries.…”
Section: Rev Esc Enfermcontrasting
confidence: 75%
See 2 more Smart Citations
“…Extensive experience gained with these patients indicates that hydrophilic devices are easier to handle, better tolerated (less urethral irritation) and microbiologically safer than the standard devices [3][4][5][6][7][8][9][10][11]. In general, when patients are given a choice, they quite invariably prefer hydrophilic to standard catheters [4,5]. On the basis of the above considerations, in the present study we evaluated the bacteriological safety and the overall comfort of a hydrophilic catheter used to perform intravesical immuno-or chemotherapy, as compared with standard catheterization.…”
Section: Introductionmentioning
confidence: 99%